Assessment of effectiveness of skin protection measures application by health service workers - Kurpiewska, Joanna; Liwkowicz, Jolanta; Nowak, Barbara (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . According to GUS data over 600 000 persons are employed in the health service (HS) sector in Poland. Contact dermatitis of the hands is one of the most frequent diseases among physicians, nurses, midwives, dentists, technicians and clinic services. Skin disorders are caused by frequent contact with water (wet work), soap, detergents, disinfectants, medical instruments and by natural rubber gloves. The skin of the hands can be protected against harmful substances with protective preparations. Objective . Our aim was to study the prevalence of self-reported skin lesions on hands and forearms in health service workers and to confirm that well-chosen barrier preparations, properly spread on the skin, provide good prevention of contact skin changes. Material and methods . Six preparations offered on the market as water-resistant (hydrophobic cream) were tested with laboratory methods. The product marked as “C” was the most effective one, so it was used in controlled application in one hospital. Results . The study was conducted on 107 persons. Skin changes such as erythema, dryness and scaling were reported by 50.5% of them. Thirty-one persons (61% nurses, 19% midwives, 7% physicians and 13% persons of other HS occupations) took part in the controlled study. A dermatologist evaluated the condition of the skin of the hands before and after application of the product. Thirty days after the onset of the study all subjects considered the condition of the skin to be much better. Conclusions . It is necessary to popularize among health service workers information about the possibility of prevention of contact dermatitis with skin protection measures i.e. barrier creams. Use of skin protection measures by HS workers will help to decrease morbidity and financial losses due to treatment, sick leave, insurance, pensions, etc.